THE EFFECT OF MARKET ORIENTATION ON GOFOOD PARTNER MARKETING PERFORMANCE IN SURABAYA - Suhelmi, Suhelmi; Susilowati, Luky; Zumrotul, Zumrotul (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
Today's digital start-ups have succeeded in creating a new trend and can solve problems in society. One that is attracting attention today is Gojek. Not only does it provide benefits from the consumer side, but Gojek can also provide benefits from the business side, one of which is by joining as a GoFood business partner or commonly called a